The Official museum directory. - American Association of Museums (New York American Association of Museums, 1971)
Annual, 1980- ; Biennial.
Supersedes Museums directory of the United States and Canada.
Keywords: Museums -- North America -- Directories; Museums -- Canada -- Directories; Museums -- United States -- Directories